The disclosure practices of Shariah non-compliant income in the annual reports of Islamic banks in Malaysia - Wan A'tirah Mahyudin
The purpose of this study was to examine the current disclosure practices of Shariah non-compliant income in the annual reports of Islamic banking institutions in Malaysia. This study investigated factors influencing the Shariah non-compliant income disclosure based on the characteristics (size, profitability and age) of Islamic banks. This study utilised five-year annual reports of sixteen Islamic banks in Malaysia to examine the extent of disclosure of the banks. A disclosure index was developed, and a dichotomous procedure was used to examine the extent of disclosure by the banks. In addition, a simple linear regression was performed to investigate the factors influencing the Shariah non-compliant income disclosure in the annual report of Islamic banks. Based on the content analysis, it was found that the extent of disclosure by Islamic banks was generally reasonable and steadily improving, but that there were still areas for improvement. The results of this study revealed that different approaches were taken by Islamic banks to disclose information about Shariah noncompliant income in which most of the banks disclosed such information in the Shariah Committee's Report, Notes to Financial Statement, and Pillar 3 Disclosure. However, very few disclosed the information in the Director's Report even though the ultimate body responsible to observe Shariah non-compliance is the board of directors. The findings of this study showed that most of the earnings of Shariah non-compliant income were derived fiom the bank's involvement in Shariah non-compliant products and services, and the failure of people and the system. The regression analysis showed that size, profitability, and the age of the banks positively influenced the disclosure of Shariah non-compliant income by Islamic banks in Malaysia even though it was not statistically significant. The results of this study contribute to the existing knowledge in the literature for addressing the concerns about Shariah compliance and reporting issues in the Islamic banking industry.